Cultural communication differences in initial public offering documentation: The case of China - Anamari Irizarry Quintero; Javier Rodríguez Ramírez; Camille Villafa\~ne-Rodríguez (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - Written communication differences across cultures can set the tone for effective or disastrous business relationships. Although English has been the go-to language in business, managers from different countries can significantly differ in how they convey the firms' information. This study explored these differences by examining the documentation presented by foreign corporations as part of their initial public offering (IPO) in the USA, particularly Chinese firms. Design/methodology/approach - This work examined cultural-related differences in written communications by looking at foreign corporations' descriptions of their strengths, strategies and challenges included in F-1 documents submitted to the Securities and Exchange Commission as part of the IPO process. The sample consisted of 97 American depositary receipts (ADRs) identified in the Bank of New York Mellon's ADR directory from 2003 to 2015. Findings - This study found that Chinese firms significantly differ from other countries' firms in depicting their strengths, strategies and challenges. Research limitations/implications - Limitations have to do with the sample size. Future research may address this by considering other depositary markets, not just the USA. Originality/value - The results will be significant for potential ADRs investors; they must be conscious of these differences in the written documentation submitted by Chinese firms compared to other foreign firms. The market should also be aware of these differences, as the Chinese seem less open to sharing information about the under spinning of their operations and financial prospects.
Keywords: G10; M10; 330; American depositary receipts (ADRs); Initial public offerings (IPOs); Intercultural communication; Cultural awareness